Взаимоотношения растений на первой стадии сукцессии растительности отвалов угольных шахт Донбасса - Жуков, С.П. (Промышленная ботаника, 2003)
The relations of plants in pioneer communities of the coal mine dumps in Donbass have been studied. Based on the further developing the method of correlations separation we’ve analysed the relationships of Ambrosia artemisiifolia L. as allergenic species requiring measures of phytocenotic control of its spread. As a result, the species for biological control of this species under the conditions of dumps coal mines have been determined.